Tuberculous spondylitis mimicking acute inflammatory demyelinating polyneuropathy: a rare presentation - N. A. Gajadeera; D. L. Porawagamage; F. G. Sivagnanam (Asian Journal of Internal Medicine)
Cervical spine is an uncommon site for tuberculous spondylitis. Clinically spinal tuberculosis (TB) can be a great mimicker due to non-specific presentations and variable progression. Hence it is important to be highly vigilant about the differential diagnoses of TB in endemic settings such as Sri Lanka as untreated disease can lead to devastating paraplegia. This case report describes a patient who presented with acute history of symptoms leading to early onset quadriplegia with areflexia mimicking an acute inflammatory demyelinating polyneuropathy supported by the nerve conduction studies, eventually diagnosed with tuberculous spondylitis during the course of the illness.